Acoustic monitoring in classrooms and computer laboratories (Research, Society and Development, 2021)
Although noise is present in most daily activities, its exposure brings harm from different spheres to human beings. In a school environment, their performance represents an invisible opponent of teaching/learning behavior, as it competes with the attention that the student should devote only to the teacher's explanation. Thus, the student is submitted to two different stimuli: the main one, characterized by the teacher's speech and which needs a good condition of intelligibility to be the focus of their attention; and the secondary, shaped by the competitive noise, which the student must be able to neglect, so that the explanation is not distorted and does not compromise the understanding of the main message. It is in this context that the present study aims to present acoustic monitoring data in classrooms and computer labs of the Federal Institute of Paraná (IFPR), Campus Umuarama. It was found that the sound pressure levels (SPL) are not in accordance with the acceptable limits for the respective spaces, recommended by the Brazilian standards that deal with the subject, and possible materials that contribute to the improvement of the acoustic conditioning of these environments were presented. schoolchildren. Finally, it was observed, among other items, that the classrooms presented SPL above the permitted level, especially the rooms with doors exposed to large circulation of people.